RESPON TANAMAN LADA (PIPER NIGRUML) VARIETAS CIINTEN TERHADAP IRADIASI SINAR GAMMA / Respons of Gamma Irradiation on Black Pepper (Piper nigrum L.) Ciinten Variety - Nur Laela Wahyuni Meilawati; Nurliani Bermawie; Agus Purwito; Dyah Manohara (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
Pepper is an introduced species and has always been propagated vegetatively, so it has narrow genetic base. High genetic diversity is necessary to produce new varieties, especially for breeding of resistance to foot rot disease. Increasing genetic diversity can be done through gamma ray irradiation. This research aims to evaluate response of black pepper Ciinten variety at seed and radicle emergence phases to gamma ray irradiation. The research was conducted in PAIR BATAN and greenhous e IMACRI from June 2014 to April 2015. The plant material was Ciinten variety at the seed and radicle emergence phases. The experimental design used was completely randomized design (CRD) with one factor which is dose of irradiation with seven levels (0, 25, 50, 75, 100, 125, 150) Gy. Each treatment consisted of three replications, each replication consisted of 60 seeds. Both phases showed significant differences in perfomances between dose in plant height, leaf length, number of leave, number of internode. Radiosensitivity of pepper on radicle emergence phase was higher than the seed phase indicated by LD50 (Lethal Dose 50). LD50 at seed phase was 68.15 Gy, whereas LD50 of the radicle emergence phase was 30 Gy. The higher irradiation dose that given to both treatment phases caused reduction in plant height, leaf length, while the number of leaves and nodes decreasing. Irradiation dose 25 dan 50 Gy in seed phase and 25 Gy in radicle emergence phase significantly increase genetic diversity base on quantitative, qualitative characters, anatomy and leaf resistence to P. capsici infection. Eighteen putative mutants resistant to infection P. capsici. Eighteen mutant putative Ciinten pepper varieties were expected to be high yielding varieties with more research in the greenhouse and in the field to determine the production and quality potential.